Descolonizar no es desmodernizar: un diálogo crítico entre S. Castro-Gómez y E. Dussel: Contestación de S. Castro-Gómez a E. Dussel (2021)
In this article we intend to develop the thesis according to which Santiago Castro-Gómez's critique of Enrique Dussel was a denaturalization of the Argentine philosopher's analysis of the modern project, in which Castro-Gómez brought to the forefront the practices of colonial legacies as a condition of possibility for the emergence of modernity, without the need to resort to the founding figure of the individual, an aspect that is present in Dussel's proposal. This thesis will be demonstrated through a critical dialogue between these two authors around the problem of modernity and coloniality from three analytical keys, postmodernity, modernity and decolonization, in order to think about the way in which colonial practices operated in the modern project through the use of the values present in modernity itself, without this implying a supposed demodernization.